Pianificazione sostenibile e qualità del progetto urbano - DOI: 10.5752/P.2316-1752.2009v16n18/19p251 - Monti, Carlo (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract New rules for town planning have been established in Italy, giving great importance to environmental protection and the preservation of natural resources (soil, water, energy....). As in other European countries, town planning has been divided into two parts, a master plan and an operational plan. That allows greater freedom in design and better quality of urban environment. The main instrument to achieve these results is Kevin Lynch’s site analysis, proposed in the early 60s. Key words : Town planning; Site analysis; Environmental protection.